Level of Cytokine Interleukin-6 and Interleukin 1-β on Infectious Rat Model Treated with Etlingera elatior (Jack) R.M. Smith Fruit Extract as Immunomodulator - Adryan Fristiohady; Wahyuni Wahyuni; Fadhliyah Malik; Muhammad Ilyas Yusuf; Wa Ode Salma; Rini Hamsidi; Fredy Talebong; Yuliansyah Yuliansyah; La Ode Muhammad Julian Purnama; Saripuddin Saripuddin; Sahidin Sahidin (Borneo Journal of Pharmacy, 2020)
Etlingera elatior (Jack) R.M Smith or locally in Southeast Sulawesi known as Wualae fruit has activity as an immunomodulator by increasing phagocytosis activity. Prior studies have been conducted to observe the effect of E. elatior as an immunomodulator, thus further study is needed to observe the production of cytokines such as IL-1β and IL-6 which are responsible for the immune responses. Etlingera elatior fruit macerated with 96% ethanol for three days and produced a total of ±74.6 g concentrated extract. Experimental animals used were divided into four groups (n=4) and treated orally once a day for seven days as follows: group I (0.5% Na CMC); group II (Stimuno®); group III (E. elatior fruit extract dose of 300 mg/kg BW); and group IV (E. elatior fruit extract dose of 400 mg/kg BW). On the eight-day, animals were infected with Staphylococcus aureus intraperitoneally and left for an hour. Thereafter, blood was collected and assayed using ELISA Kit (Elabscience rat IL-1β and Elabscience rat IL-6). Results demonstrated that group IV increased levels of IL-1β and group III and IV increased level of IL-6 (p<0.05). Increased levels of IL-1β and IL-6 are associated with phagocytosis in the immune response. In conclusion, E. elatior fruit extract at doses of 300 and 400 mg/kg BW increases levels of IL-1β and IL-6.